(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Along with salinity, low soil pH is the major constraint for growing winter crops in the south central coastal region of Bangladesh. Extensive research has been done to manage soil salinity, where managing low soil pH for crop production is scarce. The aim of the experiment was to improve sunflower (Helianthus annuus L. cv. Hybrid Unisun) yield through liming and phosphorus fertilizer application in the acidic saline soil of Amtali upazila of Barguna district, Bangladesh. During the winter season of 2024 a field experiment was carried out comprising two rates of lime 0 and 2 t ha-1 and four levels of phosphorus (P) having 0, 12, 24 and 36 kg P ha-1 using RCBD design. Lime application at 2 t ha-1 rate significantly increased stem girth, head diameter, number of seeds per head, 1000-seed weight, and seed, stover and root yields of sunflower. The application of P up to the highest level (36 kg P ha-1) significantly increased the growth and yield of sunflower. Lime application increased the soil pH by 0.72 unit compared to non-liming plot. The application of lime (2 t ha-1) along with 36 kg P ha-1 recorded the highest sunflower seed yield of 3.21 t ha-1 in the soil of Amtali upazila of Barguna district, Bangladesh. The benefit cost ratio (BCR) of different rates of P application without liming ranged from 5.28-10.09 but it decreased drastically while P was applied with lime having the BCR between 0.15-1.82. J Bangladesh Agril Univ 22(3):352-359, 2024